Highly efficient triplet–triplet annihilation upconversion in polycaprolactone: application to 3D printable architectures and microneedles. Issue 12 (20th January 2022) - Park, Jeong-Min; Lee, Haklae; Choe, Hyun-Seok; Ahn, Suk-kyun; Seong, Keum-Yong; Yang, Seung Yun; Kim, Jae-Hyuk
Abstract : This research reports the next generation of solid-state triplet–triplet annihilation upconversion (TTA-UC) host material (polycaprolactone, PCL) for highly efficient, processable, and biocompatible solid-state TTA-UC. Abstract : This research reports the next generation of solid-state triplet–triplet annihilation upconversion (TTA-UC) host material (polycaprolactone, PCL) for highly efficient, processable, and biocompatible solid-state TTA-UC. UC PCL was successfully fabricated using a drop-casting method and showed intense UC emission, moderate photostability, and an enhanced UC quantum yield (3.1%). After the characterization of its photochemical properties, the UC PCL was manipulated to form 3D UC structures and UC microneedles by using a commercially available 3D printer and thermal press molding method, respectively, and exhibited strong UC emission even after being subjected to heat manipulation. This is the first report describing an effective and processable solid-phase UC host material, thus paving the way for various applications in solar and biophotonic devices by integrating UC materials with complex 3D shapes.